Global Research Trends in Technology-Enhanced Learning (2020–2024): A Bibliometric Mapping Analysis - Nurfadilah, Nurfadilah; Nurlina, Nurlina; Bancong, Hatono (PPSDP International Journal of Education, 2025)
This study analyzes global research trends on Technology-Enhanced Learning (TEL) from 2020 to 2024 using a bibliometric mapping approach. Data were extracted from the Scopus database with the query TITLE-ABS-KEY (“technology-education” AND “learning”), yielding 747 valid documents consisting of journal articles, conference papers, and book chapters. The analysis employed Microsoft Excel, VOSviewer, and Biblioshiny to examine publication performance, collaboration networks, and thematic evolution. Results indicate a steady growth of research output, reflecting an increasing global commitment to educational transformation driven by digital innovation and artificial intelligence. The United States, China, and India emerged as the most productive countries, while leading sources such as Computers & Education and Educational Technology Research and Development dominated the publication landscape. Keyword co-occurrence mapping revealed seven thematic clusters, with e-learning, artificial intelligence, digital pedagogy, and STEM education as the most prominent themes. The findings highlight a paradigm shift from emergency remote learning during the pandemic to a sustainable integration of technology into pedagogical design. This study provides a foundational map for researchers and policymakers to navigate the evolving intellectual structure of TEL and highlights underexplored areas such as ethical AI implementation in Global South contexts and the limited empirical evidence on teacher readiness for advanced learning analytics.